2019
DOI: 10.1038/s41598-019-45056-8
|View full text |Cite
|
Sign up to set email alerts
|

Water dynamics in MCF-7 breast cancer cells: a neutron scattering descriptive study

Abstract: Water mobility in cancer cells could be a powerful parameter to predict the progression or remission of tumors. In the present descriptive work, new insight into this concept was achieved by combining neutron scattering and thermal analyses. The results provide the first step to untangle the role played by water dynamics in breast cancer cells (MCF-7) after treatment with a chemotherapy drug. By thermal analyses, the cells were probed as micrometric reservoirs of bulk-like and confined water populations. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 25 publications
3
33
1
Order By: Relevance
“…Initially, we performed DS experiments at room temperature in the microwave frequency range (0.1 to 50 GHz) that allowed us to characterize the γ-relaxation in the NTC, TC, and TC next-day . As these experiments were conducted at room temperature, the signal from bulk-like water is dominant in the γ-relaxation, and, in contrast to our previous quasi-elastic neutron scattering experiments, 6 no considerable differences between the NTC and TC were detected. This implies that spatial resolution (or, in other words, information about the momentum transfer) is critical to observe the dynamic differences in the bulk-like water populations of these cells at room temperature.…”
Section: Results and Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Initially, we performed DS experiments at room temperature in the microwave frequency range (0.1 to 50 GHz) that allowed us to characterize the γ-relaxation in the NTC, TC, and TC next-day . As these experiments were conducted at room temperature, the signal from bulk-like water is dominant in the γ-relaxation, and, in contrast to our previous quasi-elastic neutron scattering experiments, 6 no considerable differences between the NTC and TC were detected. This implies that spatial resolution (or, in other words, information about the momentum transfer) is critical to observe the dynamic differences in the bulk-like water populations of these cells at room temperature.…”
Section: Results and Discussioncontrasting
confidence: 80%
“…This is in full agreement with our previous inelastic neutron scattering experiments, where we showed that the frequencies and amplitudes of the vibrations from proteins in NTC and TC were similar. 6 …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations